INFORMACIYALÍQ JÁMIYET HÁM SHAXS RUWXÍY DÚNYASÍNÍŃ QÁLIPLESIWINIŃ ÓZ ARA BAYLANÍSLÍLÍǴÍ - Allambergenov, A.J. (ILIM hám JÁMIYET, 2024)
In the process of globalization, the formation and developmeńt of the human spiritual world in the developmeńt of information technologies is scieńtifically interpreted.